ANALYSIS OF THE PRICE TRANSMISSION OF ONIONS, GARLIC, AND LARGE RED CHILI IN INDONESIA - Inda Yesti Karmila; Musriyadi Nabiu; Ketut Sukiyono (AGRIBUSINESS JOURNAL, 2022)
The objectives study is determining the price-forming market between the producer and consumer markets of shallots, garlic, and large red chilies in Indonesia. Analyze the transmission of commodity prices of shallots, garlic, and large red chili at the level of producers to consumers. Analyze the length of time for adjusting the price of shallots, garlic, and red chilies at the price level of producer and consumers in Indonesia. Indonesia was chosen as the object of research because Indonesia which have fluctuating prices. Transmission analysis was performed using an error correction (ECM) model. In the ECM, short-term imbalances for short-term unbalanced adjustments and long-term equilibrium adjustments. The results of this study show price changes in shallot commodities occur at the producer level while in garlic and red chili commodities, price changes occur at the consumer level. In the process of transmitting shallot prices in Indonesia, the adjustment of chili prices at the consumer level experienced a lag of 5.7%, garlic commodities adjustments in garlic prices at the produce level n experienced a lag of 7.7% and in commodity onion prices the adjustment of chili prices at the producer level experienced a lag of 7% towards a long-term price balance. The long-term relationship shows that if at the time of the increase price in consumers rises, the price of chili at the producer level will also rise. The value of the ECT coefficient explains that the adjustment between the long-term correctable is 3.3%, 4.5% and 2%. This means that price adjustments to the price balance conditions on the commodity of shallots, garlic and large red chili in Indonesia take a period of 2 months.